Kualitas Mikrobiologis Udara di Salah Satu Pusat Perbelanjaan di Jakarta Selatan - Eko Pudjadi; Rima Suciyani; Innes Gania Sahira; Megga Ratnasari Pikoli (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
The airborne bacteria and fungi in parking building, playground and food court in Blok M Square, South Jakarta, were assessed in order to investigate air quality in one of the shopping center in Jakarta. The air sample was passed through plate count agar and potato dextrose agar using a single-stage multi-orifice Sampler SKC Biostage Standard. Results showed that average microbial concen-trations were 200.17, 101.17, 55, 33 CFU bacteria per m3, and 109.54, 37.69, 27.09 CFU fungi per m3 of air volume in the parking building, the children playground and the food court, respectively. The most dominating bacteria had characteristicsresembleairborne Bacillus subtilis, while the most dominating fungi wereidentified as Cryptococcus sp., Aspergillus spp., Penicillium sp. and Candida sp. The microbial concentrations were different significantly (α=0,05) inall the three areas. In addition, there were strong relationship and significant influence between the concentrations of bacteria and fungi to temperature, humidity and light intensity in in all the three areas based on Pearson correlation analysis. For today, there is no air quality standard specifically for shopping center, so the data were compared tocommon standards for indoor air quality. The concentration of bacteria and fungi met the standard regulated by TheMinistry of Health Republic of IndonesiaNo.1405/MENKES/SK/ XI/2002 about Environmental Requirements for Office and Industrial., i.e <700 CFU/m3, and acceptable according to World Health Organization (WHO) with 500 CFU/m3 as a normal condition. In any case, it is advisable to be aware ofthe spread of airborne bacteria and fungi in shopping centersthat are potentially pathogenic.